UPAYA KEPALA SEKOLAH MELALUI SUPERVISI DALAM MENINGKATKAN KREATIVITAS GURU DALAM PEMBELAJARAN DARING DI SDN 022 HARAPAN BARU - Sahippuddin (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to increase teachers’ creativity in the learning process through the efforts made by the school principal in online learning. The form of this research was school action research conducted by the principal himself, using quantitative descriptive methods. The place of the study was SDN 022 Harapan Baru, Kecamatan Kempas, with the research subjects being the teachers. The results of this study were the principal's efforts in increasing teachers’ creativity in teaching through academic supervision were successful, as evidenced by the research data. First, the teacher's creativity in preparing lesson plans got an average score of 75 with a percentage of 85%, in the good category. Second, the item created using the learning method obtained an average value of 80 with a percentage of 90% in the good category. The online learning management initiative item obtained an average value of 70 with a percentage of 80% in the good category. The student learning outcomes items obtained an average of 70 with a percentage of 80% in the good category. It can be concluded that the efforts made by the principal were successful in increasing the creativity of teachers in the learning process at SDN 022 Kempas District, Indragiri Hilir Regency.